The Low Voltage Isolation Transformer Failure Investigation: Measurements, Analysis and Lessons Learned - Boonseng, Chongrag; Boonseng, Rapeepornpat; Kularbphettong, Kunyanuth (My University, 2020)
This paper presents a case study of failure analysis for a 200kVA, 400 V isolation transformer at a semiconductor plant with a start-up with problems faced before permanent damage. The basic requirements of the acceleration of the dynamic transformer to achieve a successful start will be checked In addition, the results of the measurement of the location of the electrical parameters and the separation process are shown to indicate the cause of the error and evidence of the testimony. The results are confirmed by a failure analysis report provided by the manufacturer. This paper also addresses the obstacles that are faced due to the limited error and availability of information and how to solve the problem.
Keywords: dry-type transformer; harmonic and harmonic resonance; vibration